2021
DOI: 10.1101/2021.06.02.446732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing Hydrogen Bonds in Intact RNA from MS2 Bacteriophage Using Solid State Magic Angle Spinning NMR

Abstract: Ribonucleic acid (RNA) is a polymer with pivotal functions in many biological processes. RNA structure determination is thus a vital step towards understanding its function. The secondary structure of RNA is stabilized by hydrogen bonds formed between nucleotide base pairs and it defines the positions and shapes of functional stem-loops, internal loops, bulges, and other functional and structural elements. In this work we present a methodology for studying large intact RNA molecules using homonuclear 15N solid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Finally, the first studies on RNA at 40 kHz MAS (Yang et al, 2017;Zhao et al, 2019) and MAS ≥ 100 kHz (Marchanka et al, 2018b;Aguion et al, 2021) have been performed, reporting both assignment of resonances and identification of base pairs by sensitive 1 H-detected ssNMR spectroscopy. In the research field of phage viruses, the Goldbourt laboratory has obtained nucleotide-type assignment for very large native DNA (Sergeyev et al, 2011;Morag et al, 2014;Goldbourt, 2019) and has recently identified base pairs in native 1.2 MDa RNA from the bacteriophage MS2 (Lusky et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the first studies on RNA at 40 kHz MAS (Yang et al, 2017;Zhao et al, 2019) and MAS ≥ 100 kHz (Marchanka et al, 2018b;Aguion et al, 2021) have been performed, reporting both assignment of resonances and identification of base pairs by sensitive 1 H-detected ssNMR spectroscopy. In the research field of phage viruses, the Goldbourt laboratory has obtained nucleotide-type assignment for very large native DNA (Sergeyev et al, 2011;Morag et al, 2014;Goldbourt, 2019) and has recently identified base pairs in native 1.2 MDa RNA from the bacteriophage MS2 (Lusky et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Structural determination of RNA by ssNMR comprises several steps that include sample preparation, spin system-specific (assignment of resonances within a nucleotide spin system) and site-specific/sequential (assignment of defined spin systems to a specific residue within the RNA) assignment of resonances, and the collection of distance and angular restraints which are then used in structural calculations (Marchanka and Carlomagno, 2019) (Figure 1). While in some studies, unambiguous assignment of RNA resonances is not necessary to obtain valuable structural information (Olsen et al, 2005;Huang et al, 2010Huang et al, , 2011Yang et al, 2017;Lusky et al, 2021), in most cases, site-specific assignment of resonances is the main limiting and crucial step in structure determination by NMR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation